Perlindungan Hukum terhadap Petani yang Memiliki Keahlian dalam Pemuliaan Tanaman - Hermina Intan Talu; Jimmy Pello; Orpa J. Nobatonis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The aim of this research is to analyze the legal protection of farmers who have expertise in plant breeding. This research method uses legal research with normative research type, which is a type of doctrinal legal research which in certain contexts is known as literature study or document study. The results of this study are that legal protection for plant breeders in Indonesia is still inconsistent, especially in Law Number 12 of 1992 tends to favor large companies with financial and technological resources, while Law Number 29 of 2000 does not provide special treatment for small farmers who face procedural obstacles and high registration costs. Law No. 4/2006 has also not provided special protection to plant breeding farmers. Norm making to protect farmers in plant breeding is faced with several inhibiting factors. These factors include the lack of clear regulations on protecting the rights of traditional farmers, limited access to their participation in the rule-making process, and limited resources and legal knowledge. In addition, the dominance of industrial interests, slow bureaucracy, and lack of communication and socialization of regulations further exacerbate the gap, while favoring modern farmers ignores small and traditional farmers.